2012
DOI: 10.1177/1098300712437219
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Enablers to Implementing Individualized Positive Behavior Interventions and Supports in School Settings

Abstract: Identifying factors perceived to either hinder or support the implementation of individualized positive behavior interventions and supports (IPBIS) is essential for promoting sustainable practice. This survey study examined the extent to which schoolbased professionals (n = 293) experienced barriers and enablers and examined their perceived level of impact on hindering or supporting the implementation of IPBIS in schools. Results indicated that the most problematic barriers were also the most experienced by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 26 publications
3
72
1
1
Order By: Relevance
“…Although this well‐designed study was conducted in the natural environment, sessions were only 10 min in duration, and this does not represent comprehensive programming. The paucity of publications demonstrating comprehensive assessment and intervention may be due to the difficulty in implementing best‐practice procedures within natural settings when the severity of challenging behavior could put the child or others at risk (Bambara, Goh, Kern, & Caskie, ; Hanley, ; Kasari & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this well‐designed study was conducted in the natural environment, sessions were only 10 min in duration, and this does not represent comprehensive programming. The paucity of publications demonstrating comprehensive assessment and intervention may be due to the difficulty in implementing best‐practice procedures within natural settings when the severity of challenging behavior could put the child or others at risk (Bambara, Goh, Kern, & Caskie, ; Hanley, ; Kasari & Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that further research is needed, guided by two critical components in FBA processes in schools: (a) adoption of skills and practices in FBA and (b) team-based approaches in schools. Bambara, Goh, Kern, and Caskie (2012) found that insufficient training in FBA and personal beliefs about the benefit of traditional punishment or the result of behavior intervention that should produce rapid decreases in behavior problems were reported by school staff as perceived barriers in implementing FBA in schools. Bearing this in mind, FBA delivery skills and knowledge are important considerations.…”
Section: Issues In Implementing Functional Behavior Assessmentmentioning
confidence: 98%
“…Researchers found that administrator support was a crucial element to achieve the full implementation of PBIS (Lohrmann, Forman, Martin, & Palmieri, 2008). Without that support, any effort to sustain the initiative will likely fail (Bambara, Goh, Kern, & Caskie, 2012;Lohrmann et al, 2008). Simonsen et al (2008) also recommend at least 80 percent buy-in from teachers and staff for PBIS adoption, a reliable data system, and PBIS training for all personnel tailored to the needs of the individual school.…”
Section: Positive Behavioral Interventions and Supports (Pbis)mentioning
confidence: 99%